Temporal changes in thiol‐oxidized plasma albumin are associated with recovery from exercise‐induced muscle damage after a marathon - Christopher James; Erin M. Lloyd; Peter G. Arthur (Physiological Reports)
Abstract Exercise‐induced muscle damage (EIMD) can affect athlete performance and is a risk factor for major muscle injury. The temporal profile of thiol‐oxidized albumin, a marker of oxidative stress, has shown potential in assessing recovery from EIMD in non‐athletically trained participants but not yet in trained participants. Our primary aim was to assess whether there are changes in the level of thiol‐oxidized albumin after a marathon in athletically trained participants. Twenty participants completed a marathon and collected daily dried blood spots from 3 days prior to and 7 days after the marathon to measure thiol‐oxidized albumin using a novel methodology (OxiDx). Participants were also assessed for indirect markers of EIMD prior to and on days 2 and 5 post‐marathon. The level of thiol‐oxidized albumin peaked at 2 days and remained elevated until 5 days after the marathon and correlated with indirect measures of EIMD. Furthermore, time of recovery for thiol‐oxidized albumin varied between participants, some recovered at 3 days post‐marathon whereas others extended beyond 7 days post marathon. Tracking temporal changes in the level of thiol‐oxidized albumin has potential to be useful in managing recovery from EIMD in athletes, particularly considering the ease of the OxiDx methodology.